Implementasi Aplikasi Hijab Berbasis Android dengan Metode Canny Operator dan Template Matching Correlation - Astri Oktavianti; Winarno Sugeng; Aldrian Agusta (Maranatha University Press, 2016)
Â Abstrak — Hijab is a head covering for Muslim women. Hijab can be developed as an application that is implemented based on android. Applications hijab are scattered on android, but the application hijab which exist at present more an assortment of hijab models only. It is considered less supporting the needs of women who hijab. Because the woman was kept at this time included more selective in choosing the model that modern hijab, but in accordance with the Islamic Shari'a.Of these problems led to the idea to create applications based on android hijab, in which modern hijab model provides the appropriate guidance of Islam and to provide information based on the shape of the face veil user at the first capture the face. The methodology used in the making of this application is a method Prototype. The programming language is JAVA (Eclipse). While the method for classification process that distinguishes types of faces in this study using two methods Canny operator and Template Matching Correlation.On the Application hijab, Input as the image of the user's face to be conducted face detection process and display the results of a user's face detection process. Then display the corresponding information hijab Islamic guidance is also based on the shape of the face of the user face detection process. Face shapes used are rounded, long, oval and square with the characteristic that distinguishes every face shape as a reference. While the basics of hadith and verses in the Qur'an make reference to the appropriate information hjab Islamic guidance. With the Android-Based Application hijab is expected of the veiled women to know and implement the hijab correctly.Â Keywords — Hijab, Java (Eclipse), Â Canny operator, Template Matching Correlation.